THE RELATIONSHIP BETWEEN INCOME AND CIGARETTE CONSUMPTION WITH THE FINANCIAL WELL-BEING OF GEN Z - Dela Sifa Ramadhani; Eva Wany Wany (Income, 2025)
Cigarettes are one of the world's uncardified world health problems. The number of smokers in the world in 2015 is estimated to 1.3 billion people in which Indonesia is ranked first of the largest smokers in ASEAN with an amount of 65 million smokers and 69 percent of dominated teenagers. World Health Organization (WHO) establishes a reduction in cigarette consumption as one of the targeted NCDS global targets to be achieved by 2025 with the actions priority of tax rates of all taxes of cigarettes to reduce cigarette demand. Financial welfare is a fundamental thing to achieve in the manheuismhe son. Financial welfare reflects the administrative financial status of utuatiki undergoes a comfortable and prosperous child. . The results of the study (Wijayanti, 2023) states that the attitude of the guitarizer has a comparison to the welfare of the life. If someone has a baguan's life's attitude then will be luiruis with the preaching of the powers, so it can produce financial marketing. Evolution of income affects the consumer response as a reference in determining how much cigarette consumption this may intend to influence the financial welfare. In connection with this, this study aims to analyze the effect of individual income factors and cigarette consumption to the financial welfare of genes Z. By using a simple linear regression model. The data used is obtained from the Say of the questionnaire to the Z. GEN. The results of this study found that factor